Incidence and in-hospital outcomes of single-vessel coronary chronic total occlusion treated with percutaneous coronary intervention. (15th October 2018) - Doshi, Rajkumar; Patel, Nirav; Kalra, Rajat; Arora, Harpreet; Bajaj, Navkaranbir S.; Arora, Garima; Arora, Pankaj
Abstract: Background: Coronary chronic total occlusion (CTO) using percutaneous coronary intervention (PCI) presents a distinct challenge in the field of cardiology owing to multiple reasons including the increased risk of peri-procedural complications. We sought to explore rates of hospitalization, outcomes, use of mechanical circulatory support devices, and economic burden associated with single-vessel coronary CTO undergoing PCI for stable coronary artery disease (CAD). Methods: The National Inpatient Sample spanning from 2008 through 2014 was queried to identify hospitalizations associated with single-vessel coronary CTO-PCI for stable CAD by excluding hospitalizations with ST-elevation and non-ST elevation myocardial infarction. Survey-Specific logistic regression was used to analyze adjusted incidence of in-hospital mortality and acute renal failure. Results: A total of 109, 094 hospitalizations were identified as having single-vessel coronary CTO-PCI for stable CAD from 2008 to 2014. An increasing number of coronary CTO-PCI hospitalizations (2465 to 2688 per 100, 000 PCI procedures, Ptrend  < 0.001) with an overall in-hospital mortality of 0.5% was observed. The rate of in-hospital mortality remained unchanged (Ptrend  = 0.13), but an increasing rate of acute renal failure was observed in the multivariate-adjusted analysis (Ptrend  < 0.001). Furthermore, a rise in the utilization of intra-aortic balloon pumps and percutaneous left ventricular assist devices during single-vessel coronary CTO-PCI was noted. Taken together, these may account for increasing costs of hospitalization for single-vessel coronary CTO-PCI ($13, 909 in 2008 to $17, 729 in 2014, Ptrend  < 0.001). Conclusion: In a large retrospective study, slightly increased rates of single-vessel coronary CTO-PCI for stable CAD were observed. This is accompanied by a rise in morbidity and growing healthcare costs. Highlights: Randomized trial data suggest an unclear benefit of CTO-PCI in patients with stable CAD. Hospitalizations for single-vessel CTO-PCI have marginally increased from 2008 to 2014. Hospital deaths are stable at ~0.5%; however risk of acute renal failure has risen with CTO-PCI. Economic burden associated with single-vessel CTO-PCI for stable CAD has increased. High-volume centers (≥50 CTO-PCIs) have improved outcomes compared to low-volume centers.